2022
DOI: 10.1161/hypertensionaha.121.18503
|View full text |Cite
|
Sign up to set email alerts
|

Nalfurafine, a G-Protein–Biased KOR (Kappa Opioid Receptor) Agonist, Enhances the Diuretic Response and Limits Electrolyte Losses to Standard-of-Care Diuretics

Abstract: Nalfurafine is a G-protein–biased KOR (kappa opioid receptor) agonist that produces analgesia and lacks CNS adverse effects. Here, we examined the cardiovascular and renal responses to intravenous and oral nalfurafine alone and in combination with furosemide, hydrochlorothiazide, or amiloride. We hypothesized that nalfurafine, given its distinct mechanism of vasopressin inhibition, would increase urine output to these diuretics and limit electrolyte loss. Following catheterization, conscious Sprague-Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…KOR agonists have received attention in the past due to being non-addictive anti-nociceptive drugs that do not induce respiratory depression ( Viscusi et al, 2021 ; Wang et al, 2021 ), properties that compare favourably with those of MOR agonists such as morphine. However, they have their own distinctive side effect profiles that include stress and aversion ( Dykstra et al, 1987 ; Land et al, 2008 ; Wee and Koob, 2010 ), depression ( Knoll and Carlezon, 2010 ), sedation ( Dykstra et al, 1987 ), diuresis ( Meariman et al, 2021 ), and neuroendocrine effects (increase in serum prolactin, cortisol, and adrenocorticotropic hormone levels) ( Ko and Husbands, 2020 ). These side effects have hindered clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…KOR agonists have received attention in the past due to being non-addictive anti-nociceptive drugs that do not induce respiratory depression ( Viscusi et al, 2021 ; Wang et al, 2021 ), properties that compare favourably with those of MOR agonists such as morphine. However, they have their own distinctive side effect profiles that include stress and aversion ( Dykstra et al, 1987 ; Land et al, 2008 ; Wee and Koob, 2010 ), depression ( Knoll and Carlezon, 2010 ), sedation ( Dykstra et al, 1987 ), diuresis ( Meariman et al, 2021 ), and neuroendocrine effects (increase in serum prolactin, cortisol, and adrenocorticotropic hormone levels) ( Ko and Husbands, 2020 ). These side effects have hindered clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…It may also be that different KOP agonists have differential effects on renal excretion mechanisms. A recent study by Meariman et al 51 showed that administration of nalfurafine, a G‐protein‐biased KOP agonist had diuretic effects but significantly reduced urinary sodium and potassium excretion in water‐loaded male Sprague–Dawley rats 50 . This may be one tool useful to investigate sex differences in sodium and potassium excretion following KOP activation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work by [14] showed that hyperalgesia effects of morphine are not attributable to the binding of morphine to peripheral receptors but to central mu receptors. Kappa receptors' actions in hypothalamus and in the adrenal glands cause diuresis as a side effect [10]. Delta receptor is associated with convulsions due to actions on the thalamo-cortical areas and the hypothalamus [4].…”
Section: Discussionmentioning
confidence: 99%